2013
DOI: 10.1111/lam.12036
|View full text |Cite
|
Sign up to set email alerts
|

Salt stress-induced invasiveness of major Listeria monocytogenes serotypes

Abstract: Significance and Impact of the Study: Listeria monocytogenes 4b serotype strains are responsible for the majority of recorded invasive listeriosis outbreaks. We showed that strains of serotype 4b are not only the most virulent L. monocytogenes strains but also have the best capacity to enhance their invasiveness in response to salt stress. Our results suggest possession of effective stress response mechanisms of 4b serotype strains, which may contribute to the high infection potential of this subpopulation. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
11
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 24 publications
1
11
0
Order By: Relevance
“…Both lineage I and lineage II comprised invasive and weakly invasive strains, which varied in the ability to invade HT-29 cells up to 7.6 and almost 3 orders of magnitude, respectively. The most invasive were serogroup 4b(d,e) strains, which agrees with the results of our previous study (Wałecka-Zacharska et al 2013).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Both lineage I and lineage II comprised invasive and weakly invasive strains, which varied in the ability to invade HT-29 cells up to 7.6 and almost 3 orders of magnitude, respectively. The most invasive were serogroup 4b(d,e) strains, which agrees with the results of our previous study (Wałecka-Zacharska et al 2013).…”
Section: Discussionsupporting
confidence: 83%
“…Comparison of results presented here with our previous data on L. monocytogenes strains from human clinical cases (n=14) and food (n= 27) demonstrates that low invasive strains are more prevalent among animal population than human and food isolates (Wałecka-Zacharska et al 2013).…”
Section: Discussionmentioning
confidence: 67%
“…The human small intestine has an osmolarity equivalent to 0.3 M NaCl, requiring gastrointestinal pathogens to be highly tolerant to salt stress in order to persist in this environment and to further invade other tissues (Sleator et al ., ). Exposure to elevated osmolarity induces the expression of the σ B regulon for general stress responses and GI epithelial cell invasion (Abram et al ., ; Bae et al ., ; Walecka‐Zacharska et al ., ). Furthermore, σ B also controls the transcription of PrfA, the master virulence regulator, and the σ B and PrfA regulons significantly overlap, further emphasizing the role of osmotic stress as a primary stress and virulence signal (Ollinger et al ., ; Chaturongakul et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…In L. monocytogenes, expression of the a B factor is strongly induced by salt stress (3). Walecka-Zacharska et al (36) concluded that L. monocytogenes enhanced invasiveness in response to salt stress. Overexpression of the gene regulators ctsR, bvrA, and bvrC was observed, especially after the treatment of acid-and salt-stressed cells with synthetic pancreatic fluid.…”
Section: Discussionmentioning
confidence: 99%
“…Low pH and a high salt content may cause changes in gene expression as a result of the adaptation of L. monocytogenes to these stresses (1,13,24,36). pH values of 5.5 and a salt content of 4.5% are often found in fermented food, such as in fermented sausages, and these conditions (acid and salt stress) have therefore been used in the current microarray experiment to investigate the gene regulation of L. monocytogenes.…”
mentioning
confidence: 99%